Strategi Efektif Dalam Manajemen Gereja Untuk Membangun Penatalayanan Yang Berdaya Dan Berdampak Bagi Pemuda Kristen - Friderich Jhonnoto Dami; Hendrik A E Lao; Andrian Wira Syahputra (Jurnal Magistra, 2024)
The author discusses effective church management in order to build stewardship to create empowered and impactful Christian youth. The author also classifies contributing elements, analyzes preventing elements, and discusses ways to get past barriers to effective strategies in the church management. Author also describes the progress and innovation made by the Church as a result of its management of youth. This research uses a literature study methodology, which looks at how the church handles stewardship for youth. The findings suggest that direction and guidance, creating a supportive and inclusive environment, and integrating community outreach and service plans are all necessary components for an effective strategy. This method has encouraged and engaged youth, resulting in increased participation and positive outcomes in each youth's faith and personal development. And also shows that management can be responsible for human and financial resources, and that good data administration and an effective ministry group notably influence the congregation's expansion, and this is a method of stewardship. With any luck, this writing can offer wider advantages as well provide appreciation for leaders of the church organizations, ministers, elders, deacons, teachers and all congregation members regarding effective church management to build empowered and impactful stewardship for Christian youth.